ANALISIS PERKEMBANGAN PESERTA DIDIK BERDASARKAN USIA MASUK SEKOLAH DASAR - Arsyi Rizqia Amalia; Arita Marini; Linda Zakiah (JURNAL TARBIYAH, 2024)
The age of children when entering elementary school is something that needs to be considered in relation to the child's readiness for school. This study aims to describe the development of elementary school students based on the age of entering elementary school. The method used in this study is a descriptive research method with a quantitative approach. The subjects of this study were second grade students in elementary school. The results of the study showed that the development of elementary school students based on age when entering school showed that the highest aspect of development was the cognitive aspect while the lowest was the social-emotional aspect. The results also showed that the older the child, the more the student's readiness to follow the education program.